Volume 8: Seismic Engineering 2014
DOI: 10.1115/pvp2014-29011
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Evaluation Method for Seismic Isolation Systems of Nuclear Power Facilities: Part 4 — Failure Behavior of Crossover Piping for Seismic Isolation System

Abstract: This paper provides a part of the series titled “Development of an Evaluation Method for Seismic Isolation Systems of Nuclear Power Facilities”. This part shows the failure behavior of crossover piping installed in a seismic isolated plant. The considered crossover piping is supported on one side by an isolated building and by a non-isolated building on the other side. During an earthquake, the piping structure is deformed due to the large relative displacements between the two buildings and at the same time e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With regard to the failure mode of the crossover piping, some studies were conducted to apply seismic isolation systems to LWRs as a part of a national Japanese project (Otani et al, 2014;Otoyo et al, 2014). These studies concluded that the failure mode of the crossover piping under seismic loads was low-cycle fatigue, similar to that of the piping of ordinary non-isolated plants, through a series of dynamic tests using a 1/10 scale model and analyses.…”
Section: Overview Of the Design Codesmentioning
confidence: 99%
“…With regard to the failure mode of the crossover piping, some studies were conducted to apply seismic isolation systems to LWRs as a part of a national Japanese project (Otani et al, 2014;Otoyo et al, 2014). These studies concluded that the failure mode of the crossover piping under seismic loads was low-cycle fatigue, similar to that of the piping of ordinary non-isolated plants, through a series of dynamic tests using a 1/10 scale model and analyses.…”
Section: Overview Of the Design Codesmentioning
confidence: 99%